PENERAPAN MESIN PARUT BERBAHAN BAKAR GAS PADA USAHA MIKRO KERUPUK SAMILER DI DESA KEMASANTANI MOJOKERTO - Rijanto, Achmad; Rahayuningsih, Suesthi (Universitas Muhammadiyah Tapanuli Selatan, 2019)
This community service activity was in partnership with a samiler cracker micro entrepreneur in the Kemasantani village, Gondang sub-district, Mojokerto district. The problems faced by a partner were a partner who does not yet have a gas-fueled scarring machine, lack of knowledge and skills of a partner in the operation of gas-fueled scarring machines. The solutions to the partner's problem were to provide a gas-fueled grate machine, improve the knowledge and skills of operating a gas-fueled grate machine. The methods used were the procurement, training and assistance of gas-fueled grate machines for micro business owner. The results achieved from this dedication were a partner already had a gas-fueled scarring unit and an increase in knowledge and skills of a partner operating gas-fueled scarring by an average of 50%.